Integrated prostate cancer centers might cause an overutilization of radiotherapy for low-risk prostate cancer: A comparison of treatment trends in the United States and Germany from 2004 to 2011. Issue 1 (April 2015) - Hager, Benjamin; Kraywinkel, Klaus; Keck, Bastian; Katalinic, Alexander; Meyer, Martin; Zeissig, Sylke Ruth; Stabenow, Roland; Froehner, Michael; Huber, Johannes
Abstract Introduction Aim of the study was to analyze changes in primary treatment for low-risk prostate cancer across different healthcare systems. Materials and methods We compared "Surveillance Epidemiology and End Results" data (USA) with data from four German federal epidemiological cancer registries, both from 2004 to 2011. We excluded metastatic disease and patients aged ⩾80 years. Thereof, we identified 132, 506 (USA) and 54, 159 (Germany) patients with low-risk according to the 2014 EAU guidelines. We tested treatment trends for statistical significance with a linear regression model. Results Active treatment was radical prostatectomy (RP) in 36.1% vs. 66.2% and radiotherapy (RT) in 38.4% vs. 11.8%. No active treatment (NAT) was reported in 24.2% vs. 16.2% (p < 0.001 each). Through the study period the use of RP decreased from 37.1% to 34.2% in the USA (p = 0.04) and was constant at a mean of 66.2% in Germany (p = 0.8). The use of RT in the USA decreased from 42.8% to 31.8% (p < 0.001), while it was stable in Germany (p = 0.09). The NAT group grew from 18.0% to 33.2% in the USA (p < 0.001), while it was stable in Germany until 2009 (p = 0.3). From 2009 to 2011 there also was an increase of the NAT group in Germany from 15.2% to 19.4% (p = 0.001). Conclusion In contrast to former evidence we found the relative use of RT for low-risk prostate cancer much higher in the USA compared to Germany. The implementation of integrated prostate cancer centers in the USA might explain this observation. Deferred and defensive treatment strategies showed a steady increase in the USA. This development seems delayed in Germany by several years.